MENDORONG PENINGKATAN KINERJA MELALUI PEMBERIAN MOTIVASI DAN KESESUAIAN KOMPENSASI - Muhamad Guruh; Asep Sulaeman; , Lili Sularmi; Komarudin Komarudin (Sekolah Menengah Kejuruan (SMK) Pustek, 2023)
In particular, this study aims to determine how much influence work motivation (X1) has on the performance of employees of PT. Gunung Himun Pertamama in South Jakarta, to find out how much influence compensation (X2) has on employee performance (Y) PT. Gunung Himun Pertamama in South Jakarta and to find out how much influence work motivation (X1) and compensation (X2) have on employee performance (Y) PT. Mount Himun Pertamama in South Jakarta either partially or simultaneously. The research method used is the associative method. The sampling technique used was random sampling using a sample of 60 respondents. Data analysis used validity test, reliability test, classical assumption test, regression analysis, correlation coefficient analysis, coefficient of determination analysis and hypothesis testing. The results of this study are that work motivation has a significant effect on employee performance with the regression equation Y = 20.994 + 0.449 X1, the correlation coefficient value is 0.449 meaning that the two variables have a strong relationship with a determination coefficient of 44.9%. Hypothesis testing obtained t count > t table or (3.889 > 2.00247). Thus H0 is rejected and H1 is accepted, meaning that there is a significant influence between motivation on employee performance. Compensation has a significant effect on employee performance with the regression equation Y = 23.319 + 0.355 X2 correlation coefficient value of 0.355 meaning that the two have a strong relationship with a determination coefficient of 35.5%. Hypothesis testing obtained t count > t table or (2.408 > 2.00247). Thus H0 is rejected and H2 is accepted, meaning that there is a significant influence between compensation on employee performance. Work motivation and compensation have a significant effect on employee performance with the regression equation Y = 10.279 + 0.416X1 + 0.295X2. The correlation coefficient value obtained is 0.711, meaning that the independent variable and the dependent variable have a strong relationship with the coefficient of determination or simultaneous influence of 71.1% while the remaining 28.9% is influenced by other factors. Hypothesis testing obtained F count > F table or (11.842 > 3.16). Thus H0 is rejected and H3 is accepted. This means that there is a significant influence simultaneously between work motivation and compensation on the performance of employees of PT. Mount Himun Pertama in South Jakarta.